2009
DOI: 10.1007/s00281-009-0164-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis

Abstract: Primary biliary cirrhosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 333 publications
(409 reference statements)
5
137
0
11
Order By: Relevance
“…First, our position has always been that the antimitochondrial antibody (AMA) alone is insufficient to make a diagnosis of PBC in either humans or murine models; the diagnosis relies on evidence of autoimmune cholangitis identified on coded slides by a ''blinded'' pathologist. 1 Importantly, cholangitis can be transferred to naive Rag recipients using CD8 T cells from dnTGFbRII mice demonstrating an autoimmune component, data consistent with flow cytometry of liver subpopulations and cytokine analysis. Third, AMA standardization uses not only enzyme-linked immunosorbent assay (ELISA), but also enzyme inhibition, immunoblotting, absorption, peptide microarrays, affinity-purified antisera, and generation of large panels of mAbs, 1 not just the ELISA data of Hohenester et al In fact, the definition and measurement of AMAs always includes reactivity to MIT3, the only recombinant autoantigen approved by the Food and Drug Administration (FDA) for liver autoimmune disease.…”
Section: Replysupporting
confidence: 58%
See 1 more Smart Citation
“…First, our position has always been that the antimitochondrial antibody (AMA) alone is insufficient to make a diagnosis of PBC in either humans or murine models; the diagnosis relies on evidence of autoimmune cholangitis identified on coded slides by a ''blinded'' pathologist. 1 Importantly, cholangitis can be transferred to naive Rag recipients using CD8 T cells from dnTGFbRII mice demonstrating an autoimmune component, data consistent with flow cytometry of liver subpopulations and cytokine analysis. Third, AMA standardization uses not only enzyme-linked immunosorbent assay (ELISA), but also enzyme inhibition, immunoblotting, absorption, peptide microarrays, affinity-purified antisera, and generation of large panels of mAbs, 1 not just the ELISA data of Hohenester et al In fact, the definition and measurement of AMAs always includes reactivity to MIT3, the only recombinant autoantigen approved by the Food and Drug Administration (FDA) for liver autoimmune disease.…”
Section: Replysupporting
confidence: 58%
“…I read with great interest the article by Fontana et al 1 in which the authors demonstrate in mice that aging does not favor or worsen the accumulation of intrahepatic lipids, whereas it promotes hepatocellular injury and inflammation (nonalcoholic steatohepatitis [NASH]), due to the activation of the Fas death pathway and M1 macrophage polarization. The authors used naïve mice aged 830 CORRESPONDENCE HEPATOLOGY, August 2013…”
Section: Old Age and Steatohepatitis: A Dangerous Liaison?mentioning
confidence: 99%
“…[17][18][19][20]39,43 Our data may provide a missing pathophysiologic link in the pathogenesis of PBC, which, in our view, is based on the interplay between genetic, exogenous, and endogenous predisposing factors. [17][18][19][20]39,43 Future therapeutic approaches might, therefore, aim to further strengthen the weakened biliary HCO À 3 umbrella in PBC. 7 Advances have been made in understanding the mechanisms and sites of action of ursodeoxycholic acid (UDCA) in the therapy of chronic cholangiopathies.…”
Section: Discussionmentioning
confidence: 79%
“…23 Ischemia-type biliary lesions and nonanastomotic bile duct strictures after liver transplantation with denervation in man 42 may be a consequence of disrupted vagal acetylcholine signaling, a physiologic driving force of biliary HCO À Our data may have particular impact on the understanding of the pathogenesis and treatment of PBC. [17][18][19][20]39,43 Increasing evidence supports the view that cholangiocyte apoptosis is a driving force in the pathogenesis of PBC: It has long been demonstrated that cholangiocyte apoptosis is associated with ductular inflammation in PBC, but not PSC. 44 Furthermore, cholangiocytes of small bile ducts expose immunologically reactive PDC-E2 or PDC-E2-like protein during apoptosis, 16 which might explain, in part, the organ specificity of the immune reaction in PBC.…”
Section: Discussionmentioning
confidence: 93%
“…A PBC az 50. életév körül jelentkezik [22,23]. A "tí-pusos" PBC-s betegek 30-65 év közötti nők [2], 25 éves kor alatt ritka [22,23].…”
Section: Klinikai Tünetek Kórjelekunclassified